EXPERIMENTAL RESEARCH OF THE PROCESS OF WEAR OF MATERIALS WITH HARD COATING AND ITS SIMULATION - Малишкін, В. В.; Ходак, М. О.; Голего, М. М.; Вишневський, О. А. (Proceedings of National Aviation University, 2021)
The results of researches of tribotechnical characteristics of gas-thermal coverings like VKNA and ZhSbK alloy are considered. The tested technological modes of restoration and strengthening of surfaces of details with application of plasma drawing of heat-resistant coverings for the purpose of their use at development of recommendations for concrete conditions in repair manufacture are resulted. Empirical dependences of the wear process are obtained by mathematical modeling. The prospects of application of the given coverings for strengthening and restoration of details of units of friction of aviation equipment are shown.